Global Challenges in Energy and Environment Select Proceedings of ICEE 2018 - Sivasubramanian, V.; Subramanian, S. (Lecture Notes on Multidisciplinary Industrial Engineering, 2020)
XI, 220 p. 100 illus., 82 illus. in color.